Red light-induced structure changes in phytochrome A from Pisum sativum - Mao Oide (Nature Portfolio, 2021)
Abstract Phytochrome A (phyA) is a photoreceptor protein of plants that regulates the red/far-red light photomorphogenic responses of plants essential for growth and development. PhyA, composed of approximately 1100 amino acid residues, folds into photosensory and output signaling modules. The photosensory module covalently binds phytochromobilin as a chromophore for photoreversible interconversion between inactive red light-absorbing (Pr) and active far-red light-absorbing (Pfr) forms to act as a light-driven phosphorylation enzyme. To understand the molecular mechanism in the initial process of photomorphogenic response, we studied the molecular structures of large phyA (LphyA) from Pisum sativum, which lacks the 52 residues in the N-terminal, by small-angle X-ray scattering combined with multivariate analyses applied to molecular models predicted from the scattering profiles. According to our analyses, Pr was in a dimer and had a four-leaf shape, and the subunit was approximated as a bent rod of 175 × 50 Å. The scattering profile of Pfr was calculated from that recorded for a mixture of Pr and Pfr under red-light irradiation by using their population determined from the absorption spectrum. The Pfr dimer exhibited a butterfly shape composed of subunits with a straight rod of 175 × 50 Å. The shape differences between Pr and Pfr indicated conformational changes in the Pr/Pfr interconversion which would be essential to the interaction with protein molecules involved in transcriptional control.